GAMBARAN EPIDEMIOLOGI KUSTA PADA ANAK DAN PELAKSANAAN KEMOPROFILAKSIS KUSTA DI KOTA MATARAM - Affarah, Wahyu Sulistya (Faculty of Medicine Universitas Mataram, 2021)
Efforts to treat and prevent leprosy have improved, but in fact this disease is still difficult to eliminate and still a world health problem. Leprosy in childhood reflects the on going active transmission of the disease in the community as well as the efficiency of ongoing disease control programs. Effective planning to reduce the incidence of leprosy and its complications in children must be a priority. This cross-sectional study used a mixed of quantitative and qualitative methods. Quantitative data is obtained from secondary data on cases of child leprosy, while qualitative data is obtained from in-depth interviews with the person in charge of the leprosy program at the health center in the city of Mataram. Ms. Excel is used to analyze quantitatively and thematic test is used to analyze qualitatively (open code software). There were two cases of leprosy in children but had completed treatment and cured. The knowledge of the person in charge of the leprosy program about handling leprosy in puskesmas is quite good, but their understanding on the national strategy, especially about chemoprophylaxis is not understood comprehensively. The implementation of the leprosy prevention program at the Puskesmas has been running regularly, however currently constrained by covid-19 pandemic.